Cellular responses of normal human osteoblasts to multiple environmental stressors in vitro / Aisha Mohd Din - Mohd Din, Aisha (Institute of Graduate Studies, UiTM, 2017)
Cells respond to environmental stress via the activation of various survival pathways and may possibly end with the initiation of cell death in order to eliminate damaged cells. The ability of cells to mount an adaptive or destructive response depends on the type and duration of the stress. The response to continuous orbital fluid shear stress (OFSS), moderate hypothermia (35°C) and moderate hyperthermia (39°) in this study demonstrated an anabolic effect on Normal Human Osteoblast (NHOst) cells where the cell metabolism, differentiation and proliferation was either promoted or retained. The anabolic effect correlated with an inhibition of osteoclast activity by reducing the RANKL/OPG ratio. In response to 3 days of OFSS, increase in NHOst mitochondrial metabolism and proliferation simultaneously prevented apoptosis. Meanwhile the increase in alkaline phosphatase (ALP) activity and osteocalcin (OCN) after recovery from OFSS suggested that NHOst function was promoted.